A panoramic view of the life of Al-Rhazes, the polymath pioneer of psychopharmacology and psychiatry - Ashinze, Patrick; Unwaba Owoicho, Winner; Mafua, Nelson; Nnagha, Ekene; Akande, Eniola; Bonu, Innocent; Idris-Agbabiaka, Abdullaah; Ayodeji, Olasemo; Musa, Lukman Abiodun; Olanite, Michael; Kolawole, Tunde; Oluwafisoye-Oragbade, Oluwatosin (Journal of Global Medicine, 2025)
This work examines the life and contributions of Abū Bakr Muhammad ibn Zakariyyā al-Rāzī (865–925 AD), also known as Rhazes, a renowned Persian polymath and physician. Being famous as the father of psychiatry, psychology and pharmacology, Rhazes made significant advancements in medicine, philosophy, ethics and alchemy. His works, including influential treatises and translations of Greek medical texts, laid the groundwork for modern medical practices. As a physician and medical director in Baghdad, his humanitarian efforts were particularly aimed at aiding the poor. This biography examines Rhazes’s achievements, highlighting his interdisciplinary impact on various medical fields and natural sciences. By studying and marvelling at his contributions, we gain valuable insights into the historical evolution of medical knowledge and the foundational concepts that continue to influence contemporary medical practices.